2019
DOI: 10.48550/arxiv.1912.00681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability of Redundancy Systems with Processor Sharing

Abstract: We investigate the stability condition for redundancy-d systems where each of the servers follows a processor-sharing (PS) discipline. We allow for generally distributed job sizes, with possible dependence among the d replica sizes being governed by an arbitrary joint distribution. We establish that the stability condition is characterized by the expectation of the minimum of d replica sizes being less than the mean interarrival time per server. In the special case of identical replicas, the stability conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…When instead copies belonging to one job are identical, [3] showed that (i) ROS does not reduce the stability region, (ii) FCFS reduces the stability region and (iii) PS dramatically reduces the stability region, and this coincides with the stability region of system where all copies need to be fully served, i.e., λ < µK d . In [24], the authors show that the stability result for PS extends to generally distributed service times. In addition, they obtain the stability condition for general correlation structures among copies when studying the homogeneous redundancy-d model.…”
Section: Related Workmentioning
confidence: 98%
“…When instead copies belonging to one job are identical, [3] showed that (i) ROS does not reduce the stability region, (ii) FCFS reduces the stability region and (iii) PS dramatically reduces the stability region, and this coincides with the stability region of system where all copies need to be fully served, i.e., λ < µK d . In [24], the authors show that the stability result for PS extends to generally distributed service times. In addition, they obtain the stability condition for general correlation structures among copies when studying the homogeneous redundancy-d model.…”
Section: Related Workmentioning
confidence: 98%